(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Coleus is one among the largest and most diverse genera of the family Lamiaceae comprise of aromatic medicinal plantshaving potential therapeutic value. Economically, the members of the genus Coleus are of great importance acting as a source ofmedicines, providing food and as ornamentals. As recorded in ancient Sanskrit texts, different species of Coleus have been used fortreating various diseases including heart diseases, abdominal colic, respiratory disorders, painful micturition, insomnia, convulsionsand skin problems. This study is a comparative foliar micromorphological characteristics analysis such as variation in the size, shape,type and abundance of leaf epidermis, stomata and trichomes of the plants Coleus malabaricus, morphotype of Coleus malabaricus,Coleus zeylanicus and Coleus amboinicus.Methods: The type, size, abundance and structure of epidermis, stomata and trichomes were studied using Leitz Diaplan compoundresearch microscope fitted with Leica Qwin image analyser.Findings: The results showed the similarities and differences of the foliar micromorphological features of these plants. The epidermalpattern was quite different among the four plants but diacytic stomata and presence of both glandular and non-glandular trichomes iscommon. But the density and number of cells very considerably.Novelty and applications: A comparative foliar micro morphologic characters of Coleus malabaricus and its morphotype with Coleuszeylanicus and Coleus amboinicus of the family Lamiaceae was conducted with a view to elucidate their taxonomic significance andpresenting complementary data to aid in the identification of the species. This is a first report, especially in the case of Coleusmalabaricus.